Penerapan Metode Analytical Hierarchy Process (AHP) Dalam Pemilihan Benih Padi Unggul - Putri, Dini Ridha Dwiki; Fahlevi, Muhammad Reza; Indriani, Ulfah; Putri, Fetty Ade; Rahman, Maulia; Amali, Nailul (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Rice is the staple food source for the Indonesian nation. Quality rice is produced from superior rice seeds which have a high yield quantity. At present the agricultural sector is growing with many rice varieties emerging. Superior rice seeds are very important for farmers because rice seeds are the main factor that determine the success of rice cultivation. The existence of many choices makes farmers more careful in choosing the type of rice varieties that suit the soil structure and climatic conditions of the local agricultural environment. The Analytical Hierarchy Process (AHP) method is applied to determine the important criteria for rice varieties and to obtain alternatives that are in accordance with the environmental conditions of agricultural land. The alternatives used are the types of rice seeds in Indonesia, namely Inpari45, Baroma, Jeliteng, Pamelan, and Pamera. This Decision Support System was created to provide information and assist farmers in making decisions regarding the selection of rice seeds to be planted with the criteria of Upright Rice Height, Planting Age, Productive Saplings, and Yield Potential. By applying the AHP method to this Decision Support System, it is found that the best alternative has the highest value of 0.247.